1987
DOI: 10.1203/00006450-198710000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Growth Hormone in Stunted Head Growth after Cranial Irradiation

Abstract: ABSTRACT. The head sizes of 38 patients, growth hormone (GH) deficient following craniospinal (n = 26) or cranial irradiation (n = 12), have been assessed before (n = 38) and on completion of GH therapy (n = 15) or at the end of a similar period of observation without GH (n = 7).These results were compared to the change in head size seen in idiopathic GH deficiency following GH therapy (n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Head growth was not significantly impaired in any of the patient groups, although treatment included cranial irradiation in groups I , 2 and 4. Reduced head circumference has, however, been reported about 9 years after cranial irradiation (18). Possibly the radiation dose of 18-24 Gy in our patients was too low, or the follow up too short to show any significant changes.…”
Section: Sitting Height Armspan and Head Circumferencecontrasting
confidence: 57%
“…Head growth was not significantly impaired in any of the patient groups, although treatment included cranial irradiation in groups I , 2 and 4. Reduced head circumference has, however, been reported about 9 years after cranial irradiation (18). Possibly the radiation dose of 18-24 Gy in our patients was too low, or the follow up too short to show any significant changes.…”
Section: Sitting Height Armspan and Head Circumferencecontrasting
confidence: 57%
“…[1][2][3] Case reports and clinical studies [4][5][6][7][8][9][10][11] have found global delays in all linear craniofacial dimensions. This generates the erroneous impression of a relatively large cranium.…”
mentioning
confidence: 99%
“…Di Maio et al [14] reported a catch-up of head circumference in 5 patients with hypopituitarism after 18 months of combined treatment with rhGH and thyroxine. Similarly, Clayton et al [15] found that rhGH increased head circumference in growth-hormone deficient children but not in patients with growth retardation after cranial irradiation. Anneren et al [16], while studying the effect of rhGH in Down syndrome, found a better growth of the head in a first report, but this was not confirmed in a second [17].…”
Section: Discussionmentioning
confidence: 91%